Ploidy influences on metabolic substrate deposition of rainbow trout - Gomes, Aline Dal`olio; Vieira, Vanessa Aparecida Rocha Oliveira; Tabata, Yara Aiko; Takahashi, Neuza Sumico; Moreira, Renata Guimarães; Ribeiro, Cristiéle Da Silva [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2019)
Triploid fish are usually sterile. Thus, the energy and nutrients intended for sexual maturation may be available to enhance flesh quality and physical growth. The present study aimed to investigate differences in the metabolic substrates, lipids and proteins, between storage tissues from diploid and triploid female rainbow trout. Monthly, metabolic substrates were quantified in liver, muscle, and ovaries, which were collected during the first reproductive cycle. In general, it was possible to identify a seasonal and similar deposition of metabolites in different tissues of 2n and 3n females, mainly at early stages of gonadal maturation. However, from the stages 5-6, the ovaries showed great differences between ploidies, with higher concentration of lipids and protein in 2n females. This result reflects the incorporation of vitellogenin in oocytes, which is a process that does not occur in 3n females. It was possible to observe seasonal hepato-somatic index changes in 2n females, with higher values observed in the post-ovulatory stage, and the triploid animals showed lower values compared to 2n, with no seasonal difference. Viscero-somatic index can reflect the mobilization of substrates, with higher values found for 2n females in stage 5-6, which is the period of active mobilization of tissue substrates.
Keywords: metabolism; reproduction; triploidy; somatic indexes; Oncorhynchus mykiss